2013
DOI: 10.5354/0716-1077.2013.27418
|View full text |Cite
|
Sign up to set email alerts
|

Does corruption inhibit foreign direct investment?

Abstract: Globalization creates new opportunities for firms to invest abroad and many economies are making active efforts to attract Foreign Direct Investment (FDI) in order to promote economic growth. Decisions to invest abroad depend on a complex set of factors, but the least corrupt countries may attract more foreign direct investment because they provide a more favorable climate for investors. In this paper we investigate the impact of corruption on FDI inflows in 73 countries, over the period 1998-2008. Our results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
36
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 47 publications
5
36
0
2
Order By: Relevance
“…For example, Asiedu (2002) study showed that OPN has a positive impact on FDI inflows in African countries. Another study for 54 African countries by Sichei and Kinyondo (2012) showed similar result (see also Heshmati and Addison, 2003;Asiedu, 2006;Anyanwu, 2011;and Castro and Nunes, 2013). …”
Section: Tydl Framework To Determine the Actual Factors That Influencsupporting
confidence: 60%
See 1 more Smart Citation
“…For example, Asiedu (2002) study showed that OPN has a positive impact on FDI inflows in African countries. Another study for 54 African countries by Sichei and Kinyondo (2012) showed similar result (see also Heshmati and Addison, 2003;Asiedu, 2006;Anyanwu, 2011;and Castro and Nunes, 2013). …”
Section: Tydl Framework To Determine the Actual Factors That Influencsupporting
confidence: 60%
“…For instance, Haksoon (2010) showed that economic growth has a positive impact on FDI inflows of 271 countries. Similarly, Castro and Nunes (2013) suggested the same results of economic growth on FDI inflows for 73 countries (see also Addison and Heshmati, 2003). In Africa, Sichei and Kinyondo (2012) indicated that economic growth exerts a positive effect on FDI inflows in 45 African countries.…”
Section: Tydl Framework To Determine the Actual Factors That Influencmentioning
confidence: 50%
“…Quazi (2014), for example has used 1995-2011 panel data and found that the impact of corruption on FDI is significantly negative and robust. Castro and Nunes (2013) have investigated the impact of corruption on FDI inflows in 73 countries, over the period 1998-2008 and found that the least corrupt countries may attract more foreign direct investment because they provide a more favourable climate for investors. Belgibayeva and Plekhanov (2015) have reached a similar result as Castro and Nunes (2013), i.e.…”
Section: Direction and Sign Of Effectmentioning
confidence: 99%
“…Transparency International (1996) defines corruption as behaviors which are exhibited by politician in public sector and civil servant inappropriately and lawlessly to enrich them and their people by misusing one's power. It is accepted that corruption has potential to decrease investments especially foreign investments (Mauro, 1995;Keefer and Knack, 1996;Castro 2013). Economies with high level of corruption have more uncertainty because of high cost of doing business.…”
Section: Theoretical Frameworkmentioning
confidence: 99%